Top management incentive compensation and knowledge sharing in multinational corporations - Fey, Carl F.; Furu, Patrick (Strategic Management Journal, 2008)
Growing interest has emerged in viewing the multinational corporation as a knowledge creating and diffusing entity. The importance of sharing knowledge across organizational and national boundaries has been established in previous research. However, the question of which organizational policies lead to knowledge sharing between multinational units is still not fully understood. In particular, the link between compensation mechanisms and knowledge sharing has not received attention in previous studies. By studying 164 foreign‐owned subsidiaries located in Finland and China, this article attempts to identify the relationship between subsidiary bonus pay based on MNC‐wide performance and knowledge sharing between different units of the MNC. In line with the knowledge‐based perspective of the firm, the results suggest that incentive pay based on the collective performance of the MNC leads to greater knowledge sharing. Copyright © 2008 John Wiley & Sons, Ltd.